1-Benzyl-3-methylimidazolium tetrafluoroborate as an efficient and green reaction medium for the synthesis of pyrimido[1, 2-a]benzimidazoles. (1st April 2013) - Li, Yu-Ling; Cai, Gan; Liu, Xiao-Jun; Wang, Kai; Du, Bai-Xiang
A series of pyrimido[1, 2-a]benzimidazole derivatives has been synthesised in high yields in the ionic liquid [bmim]+ BF4–. The structures of the products were characterised by IR, 1H NMR, and HRMS spectroscopy. The reaction work-up is simple and the ionic liquid is easily separated from the products for reuse.